Sosialisasi Pemanfaatan IPTEKS Guna Meningkatkan Efektivitas Promosi UMKM Kelurahan Tanggung - Cindy Aurelia Wahyudi; Ririt Iriani Sri S; Mohammad Wahed (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
Responsibility Village is one of the Villages in Kepanjen Kidul District, Blitar City. The Responsibility Village itself has several sectors that support regional economic growth, one of which is the MSMEs sector. There is no doubt that there are many MSMEs in the Responsibilities Village and they are also very diverse. But unfortunately the development and growth of MSMEs is still hampered due to the lack of understanding and awareness of MSMEs actors about the development of science and technology. It is unfortunate that because of this, many MSMEs are still lagging behind in terms of promotion and marketing of the products they have. From these problems, the idea emerged to carry out this outreach activity